Problematika Pembentukan Karakter Islami Peserta Didik di MTs Islamiyah Bulurejo Damarwulan Kepung Kediri - Nurul Lailiyah; Riyadhotul Badi’ah (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2019)
This study discusses the problem of forming Islamic character of students at MTs Islamiyah Bulurejo Damarwulan Kepung Kediri. The approach in this study is a qualitative type case study. In collecting data used participant observation methods, in-depth interviews and documentation. The data analysis technique uses a model of several interrelated components, namely data collection, data reduction, data presentation and conclusion drawing. To check the validity of the data used extension of research, persistence of observation, and triangulation. Efforts made in overcoming the problem of character building are inviting student guardians to be invited to discussions and given direction so that there is a balance of education in schools and in the family environment. Students who still do not reflect the behavior or character of responsibility and discipline by being called to the office when going home from school to be guided again about character education continuously until there are changes in their behavior. Maximize the habituation method. In this case the habituation method in the form of the regulation is by giving a punishment in the form of reading istihgfar, reading short letters, reading the intentions of praying and cleaning the bathroom so that students can be deterrent in addition to the punishment. educational.